Transcriptional signatures in response to wheat germ agglutinin and starvation in Drosophila melanogaster larval midgut. - Li, H.M.; Sun, L.; Mittapalli, O.; Muir, W.M.; Xie, J.; Wu, J.; Schemerhorn, B.J.; Sun, W.; Pittendrigh, B.R.; Murdock, L.L. (Insect Molecular Biology, 2009)
One function of plant lectins such as wheat germ agglutinin is to serve as defences against herbivorous insects. The midgut is one critical site affected by dietary lectins. We observed marked cellular, structural and gene expression changes in the midguts of Drosophila melanogaster third instar larvae that were fed wheat germ agglutinin. Some of these changes were similar to those observed in the midguts of starved D. melanogaster. Dietary wheat germ agglutinin caused shortening, branching, swelling, distortion and in some cases disintegration of the midgut microvilli. Starvation was accompanied primarily by shortening of the microvilli. Microarray analyses revealed that dietary wheat germ agglutinin evoked differential expression of 61 transcripts; seven of these were also differentially expressed in starved D. melanogaster. The differentially transcribed gene clusters in wheat germ agglutinin-fed larvae were associated with (1) cytoskeleton organization; (2) digestive enzymes; (3) detoxification reactions; and (4) energy metabolism. Four possible transcription factor binding motifs were associated with the differentially expressed genes. One of these exhibited substantial similarity to MyoD, a transcription factor binding motif associated with cellular structures in mammals. These results are consistent with the hypothesis that wheat germ agglutinin caused a starvation-like effect and structural changes of midgut cells of D. melanogaster third-instar larvae.